Optimalisasi Layanan Administrasi Kependudukan Desa Melalui Pembinaan Aparatur Di Kecamatan Kuripan Kabupaten Probolinggo - Septiandika, Verto; Yunus, Eko Yudianto; Kristiyono, Kristiyono (Journal Of Human And Education (JAHE), 2025)
Population administration is a fundamental component of governance that plays a vital role in ensuring citizens' basic rights. However, its implementation still faces various challenges, such as the lack of competence among village officials, suboptimal service quality, and limited resources. This study aims to examine how the training and development of village officials can be an effective solution in improving the quality of population administration services.This research employs a descriptive qualitative method, focusing on the Optimization of Village Population Administration Services Through Apparatus Training in Kuripan District, Probolinggo Regency. Data were collected through observation, interviews, and documentation involving village officials, the community, and relevant stakeholders. The data analysis process includes data collection, data reduction, data presentation, and conclusion verification techniques.The results indicate that, overall, the optimization of village population administration services through the training of village officials in Kuripan District has shown significant progress, particularly in enhancing the competence of officials and implementing digital service innovations. However, to achieve better optimization, improvements are needed in technological infrastructure, increasing the number and skills of human resources, and strengthening coordination between villages, the district, and the regional government. This will ensure that policies can be implemented more effectively, and population administration services become faster, more accurate, and more inclusive for all citizens. Keywords: Optimization of Services, Village Population Administration, Apparatus Training.